The Transformation of Economic Behavior in the Digital Era: An Analysis of the Impact of Financial Literacy and Financial Inclusion on Economic Decision Making - Pamuji, Slamet; Pooja Basu (Fast in Social Sciences, 2025)
This study explores how financial literacy and financial inclusion influence economic decision-making in the digital era. By examining the integration of digital financial tools, online banking services, and mobile financial applications, individuals can make more informed, efficient, and strategic economic choices. Financial literacy equips individuals with the knowledge and skills to understand, evaluate, and manage financial products. In contrast, financial inclusion ensures equitable access to formal financial services, reducing vulnerability to economic risks. The study also highlights how digital platforms amplify both opportunities and challenges, including information overload, digital inequality, and cybersecurity risks. Implementing strategies to improve financial literacy and expand financial inclusion through education, policy support, and user-friendly digital solutions can foster responsible financial behavior, promote sustainable economic participation, and enhance personal and societal financial well-being. Ultimately, aligning financial knowledge, inclusive access, and digital capabilities transforms economic behavior, enabling individuals to make data-driven decisions that support long-term financial stability and growth.